Publicly produced knowledge for business when is it effective? - Hansen, Povl A. (Technovation)
This article discusses the process of innovation in terms of patents and knowledge transfer from public sector research institutions and private inventors to industry. It also discusses the results of the Danish patent dissemination system in relation to international results, and includes a review of what has happened to the patents that have been mediated by the public sector to industry. The great majority of the inventions patented were never produced. Most of these inventions were either not fully developed or not adjusted to market requirements. The conclusion is that it is very difficult to implement outside knowledge in commercial companies, and that public technology policy is greatly influenced by the 'science push' idea.